Factors Affecting Satisfaction With Inpatient Services Among Adult Patients Admitted to Arba Minch General Hospital, Southern Ethiopia: A Mixed Method Study - Kebede Gemeda Sabo; Kusse Urmale Mare; Hailemariam Berhe; Haftu Berhe (SAGE Publishing, 2023)
Previous studies on patient satisfaction in Ethiopia focused on satisfaction with nursing care and outpatient services. Therefore, this study aimed to assess factors affecting satisfaction with inpatient services among adult patients admitted to Arba Minch General Hospital, Southern Ethiopia. A mixed method cross-sectional study was conducted among randomly selected 462 admitted adult patients from March 7 to April 28, 2020. A standardized structured questionnaire and semi-structured interview guide were used to collect data. A total of 8 in-depth interviews were conducted to collect the qualitative data. SPSS version 20 was used to analyze the data, and a P -value <.05 in the multivariable logistic regression was used to declare the statistical significance of the predictor variables. The qualitative data was analyzed thematically. In this study, 43.7% of patients were satisfied with the inpatient services they received. Urban residences (AOR 95% CI 1.67 [1.00, 2.80]), educational status (AOR 95% CI 3.41 [1.21, 9.64]), treatment outcome (AOR 95% CI 2.28 [1.65, 4.32]), use of meal service (AOR 95% CI 0.51 [0.30, 0.85]), and duration of hospital stay (AOR 95% CI 1.98 [1.18, 2.06]) were the predictors of satisfaction with inpatient services. Compared to previous studies, the level of satisfaction with inpatient services was relatively low.